Factors associated with lost to follow-up behavior among HIV/AIDS patients undergoing ARV therapy - Ricki, Ricki Hendri Yudiawan; Nova, Nova Mega Rukmana; Nana, Nana Novariana (Universitas 'Aisyiyah Yogyakarta, 2025)
At Puskesmas (Primary Health Center) Madukoro, in May 2024, it was found that out of 46 patients undergoing antiretroviral (ARV) therapy, 10 had a history of lost to follow-up behavior, either temporarily or permanently. This represents 21.7% of patients lost to follow-up, based on the total number of patients who had ever received ARV treatment. This figure exceeds the World Health Organization (WHO) standard, which states that no more than 20% of patients should be lost to follow-up within one year. This study aims to identify the factors influencing lost to follow-up behavior among HIV/AIDS patients undergoing ARV therapy at Madukoro Public Health Center, North Lampung Regency. A descriptive-analytic design was used, employing a quantitative research method with a cross-sectional approach. The study population consisted of all 46 HIV/AIDS patients at the health center receiving ARV treatment, with total sampling applied. The findings revealed a significant relationship between perceived vulnerability and lost to follow-up behavior (p = 0.000), perceived severity and lost to follow-up behavior (p = 0.000), and perceived barriers and lost to follow-up behavior (p = 0.001). However, there was no significant relationship between perceived benefits and lost to follow-up behavior (p = 0.169). There was also a significant relationship between self-efficacy and lost to follow-up behavior (p = 0.001), as well as between environmental support and lost to follow-up behavior (p = 0.000). It is recommended that the Head of Madukoro Public Health Center disseminate the results of this study to the staff responsible for the HIV P2 Program, healthcare workers, and other employees in order to develop appropriate strategies or work programs to prevent lost to follow-up cases among HIV/AIDS patients.